Novel mouse model of left ventricular pressure overload and infarction causing predictable ventricular remodelling and progression to heart failure. (January 2015) - Weinheimer, Carla J; Lai, Ling; Kelly, Daniel P; Kovacs, Attila
Summary Mouse surgical models are important tools for evaluating mechanisms of human cardiac disease. The clinically relevant comorbidities of hypertension and ischaemia have not been explored in mice. We have developed a surgical approach that combines transverse aortic constriction and distal left anterior coronary ligation (MI) to produce a gradual and predictable progression of adverse left ventricular (LV) remodelling that leads to heart failure (HF). Mice received either sham, MI alone, transverse aortic constriction alone or HF surgery. Infarct size and LV remodelling were evaluated by serial 2‐D echocardiograms. Transverse aortic constriction gradients were measured by the Doppler velocity–time integral ratio between constricted and proximal aortic velocities. At 4 weeks, hearts were weighed and analysed for histology and brain natriuretic peptide, a molecular marker of HF. Echocardiographic analysis of segmental wall motion scores showed similarly small apical infarct sizes in the MI and HF groups at day 1 postsurgery. MI alone showed little change in infarct size over 4 weeks (0.26 ± 0.02 to 0.27 ± 0.04, P = 0.77); however, HF mice showed infarct expansion (0.25 ± 0.06 to 0.39 ± 0.09, P < 0.05). HF mice also showed LV remodelling with increases in LV volumes (1 day = 36.5 ± 5.2 mL, 28 days = 89.1 ± 16.0 mL) versus no significant changes in the other groups. Furthermore, systolic function progressively deteriorated in the HF group only (ejection fraction, 1 day = 55.6 ± 3.6%, 28 days = 17.6 ± 4.1%, P < 0.05) with an increase of brain natriuretic peptide by 3.5‐fold. This surgical model of pressure overload in the setting of a small infarction causes progressive deterioration of cardiac structural and functional properties, and provides a clinically relevant tool to study adverse LV remodelling and heart failure.